DIARY OF A MOTHER IN A MODERN FAMILY AND ITS ROLE IN THE FORMATION OF ATTITUDE TOWARDS THE CHILD - Romenkova, Valentīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The study is devoted to factors of development of mother’s attitude towards her child and the reflection of this attitude by keeping a diary. Keeping of mother’s diary became common in privileged circles only in late 19th century. Scientists recommended it as a means of professionalization of motherhood, to improve the quality of childcare, and as an aid for pediatric control. Mother’s diary was preceded by scientist diaries, which, in fact, became first scientific sources when assessing child’s development.Currently there are new issues affecting the relationship between mother and child. They concern the family – the environment that takes in the child and determines the direction of his development. Issues include the loss of social significance of motherhood, promotion of the “desired” child, propaganda of maternal realization in her career, having fewer children and other phenomena that did not exist before.As a result of having fewer children, the expectant mother has little contact with babies before the birth of her own, she does not acquire communication experience with younger brothers or sisters, which reduces the ability to understand and accept her own children.If in the relatively recent past it was possible to speak of a “natural” motherhood – rich, multi-generational experience of feeding and nurturing children, then in the so-called developed society motherhood (generalized social attitudes) is forced to rely on the experience of the new mother herself, who chooses a method to make up for the deficiencies in maternal education. Therefore, the theme of the study of mother’s characteristics effect on the emotional, moral, and spiritual development is to be actively developed and topical.Mother’s diary is a means to improve the educational self-analysis of the mother and the reflection of her love and affection to the child.